147 CD155 blockade boosts alloreactive natural killer cell antitumor effects against osteosarcoma. (10th December 2020) - Cho, Monica; Phillips, Madison; Song, Longzhen; Erbe, Amy; Capitini, Christian
Abstract : Background: Pediatric patients with relapsed and refractory osteosarcoma have poor prognoses with few treatment options. Allogeneic bone marrow transplant (BMT) has not yet shown a graft-versus-tumor (GVT) effect for osteosarcoma. Natural killer (NK) cells demonstrate antitumor activity against osteosarcoma, but adoptively transferred NK cells have limited proliferation, cytotoxicity, and persistence in vivo. To enhance an NK-specific GVT effect, we propose blocking the poliovirus receptor CD155 checkpoint molecule, which is overexpressed on osteosarcoma and can engage both activating and inhibitory receptors on NK cells. The impact of CD155 blockade on GVT and graft-versus-host-disease (GVHD) is unknown. Methods: NK cells from C57BL/6 (B6) mice were expanded with recombinant IL-15/IL-15R and analyzed by flow cytometry. Cytotoxicity assays were performed with IL-15 expanded B6 NK cells and mKate2-expressing K7M2 murine osteosarcoma at a 1:1 ratio with blockade of CD155 and CD155 ligands. To test efficacy of NK cell infusion and CD155 blockade after allogeneic BMT, BALB/c mice were lethally irradiated, transplanted with allogeneic B6 bone marrow, and challenged with luciferase-expressing K7M2 on day 0. At day 7, mice received IL-15 expanded B6 NK cells intravenously with either anti-IgG control or anti-CD155 antibody intraperitoneally and IL-2 subcutaneously on days 7 and 11. Mice were monitored for tumor growth by bioluminescence, and toxicity by GVHD using weight loss and clinical scores. Results: Compared to unexpanded murine NK cells, IL-15 expanded NK cells (n = 6) show increased expression of NKG2D (65.33 ± 10.77% NKG2D+, p = 0.0077; 1030 ± 177.0 MFI, p = 0.0101) and an increased ratio of the CD155 activating (CD226) to inhibitory (TIGIT) ligand expression (11.71 ± 4.121, p = 0.0362). In cytotoxicity assays with IL-15 expanded allogeneic murine NK cells (n = 3 replicates), CD155 blockade enhances K7M2 osteosarcoma lysis (60.62 ± 3.19%, p = 0.0189) compared to IgG control (29.01 ± 7.66%). CD226 blockade decreased tumor killing (10.62 ± 8.51%, p = 0.0053) compared to CD155 blockade. In vivo allogeneic murine NK cell infusion and anti-CD155 antibody treatment after allogeneic BMT decreased tumor area under the curve by 44.3% compared to IgG control, without exacerbating GVHD. Conclusions: These findings demonstrate that blockade of CD155 enhances an allogeneic NK cell-specific GVT effect for osteosarcoma treatment without exacerbating GVHD. CD155 blockade has the potential to improve usage of allogeneic BMT and NK cell adoptive immunotherapy as a combination treatment for osteosarcoma, and perhaps other pediatric sarcomas. Acknowledgements: This work was supported by grants from the National Institute of General Medical Sciences/NIH T32 GM008692 and Training in Cancer Biology Training Grant NIH T32 CA009135 (to MMC), St. Baldrick's Stand up to Cancer (SU2C) Pediatric Dream Team Translational Research Grant SU2C-AACR-DT-27-17, NCI/NIH R01 CA215461, American Cancer Society Research Scholar Grant RSG- 18-104-01-LIB, and the Midwest Athletes Against Childhood Cancer (MACC) Fund (to CMC). SU2C is a division of the Entertainment Industry Foundation. Research grants are administered by the American Association for Cancer Research, the scientific partner of SU2C. The contents of this article do not necessarily reflect the views or policies of the Department of Health and Human Services, nor does mention of trade names, commercial products, or organizations imply endorsement by the US government.